Anticipated climate changes reveal shifting in habitat suitability of high-altitude selaginellas in Java, Indonesia - AHMAD DWI SETYAWAN; Jatna Supriatna; Nisyawati; Ilyas Nursamsi; SUTARNO SUTARNO; SUGIYARTO SUGIYARTO; SUNARTO SUNARTO; Prakash Pradan; SUGENG BUDIHARTA; ARI PITOYO; SAPTA SUHARDONO; PRABANG SETYONO; MUHAMMAD INDRAWAN (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Setyawan AD, Supriatna J, Nisyawati, Nursamsi I, Sutarno, Sugiyarto, Sunarto, Pradan P, Budiharta S, Pitoyo A, Suhardono S, Setyono P, Indrawan M. 2020. Anticipated climate changes reveal shifting in habitat suitability of high-altitude selaginellas in Java, Indonesia. Biodiversitas 21: 5482-5497. High-altitude ecosystems with humid and cool climate are the preferred habitat for some Selaginella species (selaginellas). Such habitats are available in Java, Indonesia, which also has fertile soils with rich mineral contents resulted from volcanic activities. However, the high-altitude ecosystems in Java are threatened by various anthropogenic activities as well as changes in climate conditions, potentially affecting some Selaginella species. This study aimed to investigate the shift in suitable habitat of four species of high-altitude Selaginella spp. (Selaginella involvens, S. opaca, S. ornata, and S. remotifolia) in Java Island under current and future climate conditions predicted by several representative greenhouse gas concentration pathways. Presence data of Selaginella localities were collected from field survey between 2007 and 2014 across the island, as well as occurrence points from the Global Biodiversity Information Facility database. A total of 1,721 occurrence points data along with environmental and climate data were used to develop species distribution models using MaxEnt. Future habitat distributions were projected under four climate scenarios to see the shift in suitable habitat and altitudinal ranges. The results showed that the distribution of the four high-altitude Selaginella species are strongly influenced by altitude, annual average temperature, and annual rainfall. In the present time, 37.32% (48,974 km2) of the area of Java has been predicted to be suitable for high-altitude Selaginella. Under the optimistic climate scenario (RCP 2.6), the highly suitable area will likely to decrease by almost 35% in the year 2080, whereas the medium and low suitable areas will reduce by about 37.2% and 18.3%, respectively. Under the pessimistic scenario (RCP 8.5), about 21.2% of low suitable areas will be lost in 2080, whereas the medium and highly suitable areas are predicted to decrease by around 38.1% and 33.4%, respectively. Under the pessimistic scenario, there will be upward shift by 51.1 m in the year 2030 from the current’s mean altitude and will shift by almost 150 m in the year 2080. The maximum altitude of predicted suitable habitat is also predicted to increase to reach almost 3500 m asl in the year 2080. The results of this study imply that habitat shift of four high-altitude Selaginella species varies depending on the scenario, but in all cases, the losses are greater than gains.